Chronic p27Kip1 Induction by Dexamethasone Causes Senescence Phenotype and Permanent Cell Cycle Blockade in Lung Adenocarcinoma Cells Over-expressing Glucocorticoid Receptor. Issue 1 (December 2018) - Patki, Mugdha; McFall, Thomas; Rosati, Rayna; Huang, Yanfang; Malysa, Agnes; Polin, Lisa; Fielder, Abigail; Wilson, Mike; Lonardo, Fulvio; Back, Jessica; Li, Jing; Matherly, Larry; et al.
Abstract Dexamethasone (Dex), co-administered to lung adenocarcinoma patients with pemetrexed chemotherapy, protects against pemetrexed cytotoxicity by inducing reversible G1 arrest, reflected by the effect of Dex on FLT-PET images of patient tumors. However, perioperative Dex treatment increases survival but the mechanism is unknown. In cells with glucocorticoid receptor-α (GR) expression corresponding to higher clinical tumor levels, Dex-induced growth arrest was followed by marked cell expansion, beta-galactosidase expression and Ki67 negativity, despite variable p53 and K-RAS status. Dex induced a transient early surge in p21Cip1 . However, a progressive, irreversible loss of clonogenic growth, whose time of onset was dependent on GR level and Dex dose, was independent of p21Cip1 and caused by gradual accumulation of p27Kip1 due to transcriptional activation of p27Kip1 by Dex. This effect was independent of canonical pathways of senescence or p27Kip1 regulation. Thein vitro observations were reflected by growth suppression and P27Kip1 induction in GR-overexpressing tumor xenografts compared with isogenic low-GR tumors. Extended Dex treatment induces irreversible cell cycle blockade and a senescence phenotype through chronic activation of the p27Kip1 gene in GR overexpressing lung tumor cell populations and hence could improve outcome of surgery/pemetrexed chemotherapy and sensitize tumors to immunotherapy.